PRAKTIK PENANGANAN PERTAMA LUKA BAKAR PADA IBU RUMAH TANGGA DI WILAYAH SLEMAN YOGYAKARTA - Muhamat Nofiyanto; Novita Nirmalasari (Universitas Jenderal Achmad Yani Yogyakarta, 2020)
Background: Burns are the most potential type of injury experienced by housewives. Improper first aid burns can worsen the condition. Objective: To determine the first aid practice of burns incidents among housewives in Sleman region Yogyakarta. Methods: Descriptive design with a naturalist approach was used in this study. A total of 84 respondents were selected using simple random sampling technique with the criteria of housewives who are still actively doing activities in the kitchen, as well as other household activities. Data collection uses a questionnaire with closed and open combination question types. Data analysis was performed descriptively. Results: A total of 5 aspects of the first aid of burns are appropriate (Running immediately during a fire in the house (47.6%); releasing jewelry (58.3%); splashing the wound with cold running water (54.8%); not watering if more than 3 hours (86.9%); and let the bullae break apart (66.7%)). There are still 3 aspects that are not yet right (running while ducking when trapped (47.6%); removing clothes (42.9%); and length of time watering <5 minutes (50%)). Conclusion: Not all aspects of the first aid are done properly. Health education and health promotion efforts are needed to improve better practice of burns first aid.